2010
DOI: 10.1111/j.1745-6606.2010.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Financial Education on the Financial Knowledge of High School Students

Abstract: This study investigated the effects of a financial education program on high school students' knowledge of personal finance. A comparison of pretest and posttest scores achieved on a reliable and valid thirty-item instrument suggested that the Financing Your Future curriculum increased financial knowledge across many concepts. The scores increased regardless of the course in which the curriculum was used and across student characteristics. The assessment contributes to the growing literature showing that a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(155 citation statements)
references
References 11 publications
8
141
3
3
Order By: Relevance
“…Many studies have found significant gender differences in financial literacy of high school students with males outperforming females (e.g., Varcoe et al 2005;Danes and Haberman 2007;Hanna et al 2010;Butters and Asarta 2011;Butters et al 2012). However, Walstad et al (2010) find no significant gender differences in financial literacy among high school students after participating in an intervention program, which is an encouraging sign that the gender gap can be closed by financial education.…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have found significant gender differences in financial literacy of high school students with males outperforming females (e.g., Varcoe et al 2005;Danes and Haberman 2007;Hanna et al 2010;Butters and Asarta 2011;Butters et al 2012). However, Walstad et al (2010) find no significant gender differences in financial literacy among high school students after participating in an intervention program, which is an encouraging sign that the gender gap can be closed by financial education.…”
Section: Introductionmentioning
confidence: 94%
“…These properties suggest that the samples are comparable once weighted. 27 For model 2, on the contrary, the support -although also common -is more sparse.…”
Section: First Step: Probability Of Participation In the Programmentioning
confidence: 99%
“…Some experiments suggest that short …nancial literacy courses do increase …nancial knowledge. Walstad et al (2010) show that a video on …nancial literacy to high school students increased scores in …nancial knowledge exams substantially. Bruhn et al (2013) conduct a randomized experiment that randomly assigns a 78-hours course across Brazilian states.…”
mentioning
confidence: 90%
“…The literature usually approaches the topic as follows: A particular financial education intervention is analyzed with respect to its impact on measured financial literacy and-in most assessments-on financial behavior. One way to elicit potential changes in financial literacy levels involves measuring test-based literacy scores prior to educating subjects about the financial matters of interest and at some point in time after they have received the respective manipulation (e.g., Walstad et al 2010). Alternatively, the financial literacy scores of a treatment and a control group are contrasted after a given educational intervention (e.g., Lührmann et al 2015).…”
Section: Selected Financial Education Initiatives and The Costs Of Fimentioning
confidence: 99%
“…Financial literacy, financial advice, and financial behavior 621 Walstad et al 2010;Heinberg et al 2010;Lührmann et al 2015) as well as financial behavior (e.g., Bernheim et al 2001;Servon and Kaestner 2008;Clark et al 2015;Lührmann et al 2015). The literature usually approaches the topic as follows: A particular financial education intervention is analyzed with respect to its impact on measured financial literacy and-in most assessments-on financial behavior.…”
Section: Selected Financial Education Initiatives and The Costs Of Fimentioning
confidence: 99%